Economic analysis for Australian Seafood Chains: development and application of a generic value-chain model - Nath, T.; Islam, M.; Howieson, Janet (Centre of Excellence Science Seafood & Health (CESSH), 2011)
This report is the result of a study undertaken by the Centre of Excellence Science Seafood & Health (CESSH) and the Department of Agriculture and Food Western Australia (DAFWA) as part of the Seafood CRC Project improving the Supply chain for selected WA Seafood Products The primary objectives of this study are to: -develop a generic value chain model for Australian seafood industries with a future aim to apply the model to quantify the impacts of interventions (either policy or research innovations) on the industries economic performance; -apply the model on a trial basis on three participating fin-fish companies in Western Australia; and -to understand their share of value added contribution to the economy along the whole supply chain.The report presents briefly the theory, concepts and steps used to develop a generic value chain model for Australian Seafood Industry (ASI) and then describes the structure, assumptions and results of the “Value Chain” models for three Fin-fish company cases (company names are kept anonymous due to their business and data confidentiality agreements). The contents of this report are arranged in 6 sections. The theory, modelling procedures, and application of the generic model are described in Section 2, 3 and 4 respectively. Section 5 provides summary results and relevant discussion on the contributions of three fin-fish companies operating in WA. Section 6 presents concluding comments.